Kosmologi Agama Islam dan Budha - Sanurdi Sanurdi (LPPM IAIN Sorong, 2016)
In Islam, the relationship between the individual and the natural environment built by a certain moral perception is derived from God’s creation and the role given to them on earth. These natural components created with diverse by God, and man is a vital part of the creation and to be continuous measured. Human’s role not only toenjoy, use and exploit the natural environment, but also to maintain, protect and support the other creatures. At the same time, Buddha also taught the same thing about 2500 years ago. According to the Buddhist view, the universe is vast, in the universe there is a solar system whose numbers cannot be calculated. According to Buddhism as illustrated in the sermon-sermon addressed to his followers are not contained descriptions of metaphysics or divinity clearly. When Buddha pressed with questions by his disciples about these issues, then he refrains Always with his words as follows: “Therefore, O students who do not regard it as explained everything that I do not explain, and suppose as explained everything that I have explained.”This article compares cosmology in Islamic and Buddhist perspectives